1991
DOI: 10.1073/pnas.88.2.642
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of thymic epithelial cells in promoting T-lymphocyte differentiation in vivo.

Abstract: To study in vivo the contribution of different thymic epithelial cells to T-lymphocyte differentiation, we have established several nontransformed thymic epithelial cell lines and developed an in vivo assay, not involving exposure to drugs or radiation, that permitted us to study the capacity of these epithelial lines to support T-cell differentiation. We found that cell lines EA2 and ET, which express markers of cortical epithelial cells, produce interleukin 7 mRNA and after being

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 35 publications
1
26
0
Order By: Relevance
“…The Tcr b-Jbl probe (400-bp PvuII-PstI fragment), the Tcr y-J1 probe (1.2-kb AvaI-HindIII fragment), the Tcr P-Jpl probe (3.3-kb BamHI-EcoRI fragment), the Tcr P-JP2 probe (0.75-kb HindIII-EcoRI fragment) (36), the pJll probe (1.9-kb BamHI-EcoRI fragment) specific for the Ig JH gene (15), the 0.42-kb XhoI-PstI fragment of the CA1 mouse cDNA (2), and the 2.6-kb HindIII-BamHI fragment containing the kappa exon (43) were used to assess the state of Tcr and Ig genes. The PB1O A T3-y cDNA specific for mouse CD3--y (0.9-kb HindIII-EcoRI fragment) (12), the M6-BSK cDNA specific for mouse RAG-1 (1.4-kb EcoRI-EcoRI fragment), the MR2-1 cDNA specific for RAG-2 (1.0-kb PstI-PstI fragment) (28), the PuCN374 cDNA specific for the c,u Ig chain (1.3-kb BamHI-BamHI fragment) (18), the pZ183-la cDNA specific for mouse X5 (0.7-kb HindII-XhoI fragment), the pZ121 cDNA specific for mouse Vpre-B1 (0.9-kb EcoRI fragment) (14), the 0.94-kb EcoRI-BglII fragment of the MB-1 cDNA (39), the 1.1-kb PstI-PstI cDNA fragment specific for the 0-actin gene (kind gift of Susan Carson, Basel Institute for Immunology, Basel, Switzerland), and IL-la (1.9-kb BamHI-BamHI), IL-2 (1-kb XhoI-XhoI), IL-3 (0.37-kb HindIII-XbaI), IL-4 (0.3-kb RsaI-RsaI), IL-5 (0.43-kb XhoIXhoI), IL-6 (0.65-kb EcoRI-BglII), IL-7 (0.45-kb SstIHindIII) (5,40), and Steel factor (SF) (0.83-kb XhoI-XhoI) (32a) probes were used in Northern blot assays.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Tcr b-Jbl probe (400-bp PvuII-PstI fragment), the Tcr y-J1 probe (1.2-kb AvaI-HindIII fragment), the Tcr P-Jpl probe (3.3-kb BamHI-EcoRI fragment), the Tcr P-JP2 probe (0.75-kb HindIII-EcoRI fragment) (36), the pJll probe (1.9-kb BamHI-EcoRI fragment) specific for the Ig JH gene (15), the 0.42-kb XhoI-PstI fragment of the CA1 mouse cDNA (2), and the 2.6-kb HindIII-BamHI fragment containing the kappa exon (43) were used to assess the state of Tcr and Ig genes. The PB1O A T3-y cDNA specific for mouse CD3--y (0.9-kb HindIII-EcoRI fragment) (12), the M6-BSK cDNA specific for mouse RAG-1 (1.4-kb EcoRI-EcoRI fragment), the MR2-1 cDNA specific for RAG-2 (1.0-kb PstI-PstI fragment) (28), the PuCN374 cDNA specific for the c,u Ig chain (1.3-kb BamHI-BamHI fragment) (18), the pZ183-la cDNA specific for mouse X5 (0.7-kb HindII-XhoI fragment), the pZ121 cDNA specific for mouse Vpre-B1 (0.9-kb EcoRI fragment) (14), the 0.94-kb EcoRI-BglII fragment of the MB-1 cDNA (39), the 1.1-kb PstI-PstI cDNA fragment specific for the 0-actin gene (kind gift of Susan Carson, Basel Institute for Immunology, Basel, Switzerland), and IL-la (1.9-kb BamHI-BamHI), IL-2 (1-kb XhoI-XhoI), IL-3 (0.37-kb HindIII-XbaI), IL-4 (0.3-kb RsaI-RsaI), IL-5 (0.43-kb XhoIXhoI), IL-6 (0.65-kb EcoRI-BglII), IL-7 (0.45-kb SstIHindIII) (5,40), and Steel factor (SF) (0.83-kb XhoI-XhoI) (32a) probes were used in Northern blot assays.…”
Section: Methodsmentioning
confidence: 99%
“…The tubes were centrifuged, and the cells were washed once, and diluted 1:15 in culture medium, and distributed in new six-well Costar plates. The FLS4.1 stromal cells were expanded, several aliquots were frozen (in IMDM containing 20% FCS and 14% dimethyl sulfoxide), and some cells were used to determine their phenotype by immunofluorescence staining and flow fluorocytometry (FCM) analysis (see below) before and after cell membrane permeabilization with digitonin as described earlier (5).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to define the potential interaction of IL-7 secreting cells in colorectal cancer and the immune system, we have examined freshly harvested cancer specimens for IL-7 mRNA expression and protein production. To this end, only a limited number of natural IL-7 sources, including bone marrowderived stromal cells or thymic epithelial cells, have been described [19]. IL-7 is a growth factor for thymocytes, supports the gowth of pre-B cells, induces proliferation, augments immune effector cell functions in CD4 þ and CD8 þ T-cells, and induces cytokine and tumouricidal activity in monocytes [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…IL-7 is produced by stromal cell populations throughout the body 15 and is produced in high concentrations by thymic epithelium. 16,17 Animal models have shown that IL-7 is required for early thymocyte development and supraphysiologic doses of IL-7 enhance thymopoiesis. 13,[18][19][20] Thus, IL-7 potentially holds promise as an immunorestorative agent in the setting of allogeneic BMT.…”
Section: Introductionmentioning
confidence: 99%